Three-dimensional structure of human β-defensin 28 via homology modelling and molecular dynamics - Kwak, Sang Kyu (2013)
The 3D structure of the human β-defensin 28 (HBD-28) has been investigated via homology modelling and molecular dynamics (MD) approach. With known high-resolution structures of HBD-2 and -3, single- and multiple-template sequence alignments are applied to find highly probable candidates for HBD-28, which are in turn refined through MD simulations in pure water and 50% trifluoroethanol/water mixture. The models obtained from homology modelling were assessed by protein structure validation software suite, which includes Procheck, MolProbity, Verify-3D and various structure validation tools. We found that modelling quality is proportionally related to the sequence alignment accuracy. In comparison with circular dichroism experimental data as well as stabilities of β-sheets and α-helix, HBD-28 with a reliable 3D structure was found.